Synchronous or Asynchronous Learning: That’s the Question of BACOM Learners! - Reynaldo R. Vasquez; Lesly Ann D. Doclis; Joseph Bello Quinto (Halu Oleo University, 2022)
Due to the COVID-19 pandemic, the delivery of education through distance learning has become a necessity. Students have to learn from their instructors in an online platform in two methods: synchronous and asynchronous learning. With all these pieces of information in mind, this study was conducted to examine the preferences of 143 Bachelor of Arts in Communication (BACOM) learners in one state university in Cordillera Administrative Region, Philippines regarding synchronous and asynchronous learning through a valid and reliable questionnaire distributed via Google Form. In a nutshell, more BACOM learners preferred synchronous learning because it allows for collective learning and interactions in real-time which can alleviate the sense of isolation that asynchronous learning brings, and they found it easier and more manageable to navigate synchronous learning than asynchronous learning. Notably, second-year BACOM learners recorded the highest average preference on synchronous learning, while the first-year BACOM learners recorded the highest average preference on asynchronous learning. While there is no significant difference in moderate preference according to year levels, it still varies from year level to year level. This poses an area for future work where if Face-to-Face classes are still not attainable, hybrid learning, which is a combination of synchronous and asynchronous learning, can be tested to prioritize the learning progression of every learner.